Alternative Pathways to Complexity A Collection of Essays on Architecture, Economics, Power, and Cross-Cultural Analysis - Fargher, Lane F.; Heredia Espinoza, Verenice Y. (University Press of Colorado, 2016)
"[T]he volume represents an important contribution to the examination of issues for which Blanton has furthered scholarship, organized as three sections with cases from Mesoamerica, the Old World, and cross-cultural studies." -American Antiquity. Alternative Pathways to Complexity focuses on the themes of architecture, economics, and power in the evolution of complex societies. Case studies from Mesoamerica, Asia, Africa, and Europe examine the relationship between political structures and economic configurations of ancient chiefdoms and states through a framework of comparative archaeology.